Lung function and respiratory outcomes in teenage boys and girls born very prematurely. Issue 3 (7th January 2020) - Harris, Christopher; Zivanovic, Sanja; Lunt, Alan; Calvert, Sandy; Bisquera, Alessandra; Marlow, Neil; Peacock, Janet L.; Greenough, Anne
Abstract: Objectives: Male sex in prematurely born infants has been associated with worse respiratory outcomes in early childhood. Working Hypothesis: Respiratory outcomes at 11 to 14 years of age in children born very prematurely and routinely exposed to antenatal corticosteroids and postnatal surfactant would differ according to sex. Study Design: Analysis of follow‐up data. Patient‐Subject Selection: Three hundred and nineteen children born before 29 weeks of gestational age from the United Kingdom Oscillation Study. Methodology: Spirometry was used to assess forced expiratory flow at 75%, 50%, and 25% of expired vital capacity (FEF75, FEF50, and FEF25 ), forced expiratory volume in 1 second (FEV1 ), peak expiratory flow (PEF), and forced vital capacity (FVC). Lung volumes were measured using a helium dilution technique (FRCHe ) and by plethysmography (FRCpleth ). Total lung capacity (TLC) and residual volume (RV) were calculated. Mean lung function measurements were compared using linear mixed models and reported as unadjusted and adjusted for neonatal and age 11 to 14 years factors. The participants also completed health questionnaires and provided a urine sample for assessment of passive or active smoking. Results: Three (FEF25, FEF25‐75, FEV1 ) lung function measures showed significant differences in favor of females after adjustment. The percentage of children with abnormal lung function (below 5th centile for normal) had adjusted differences between 10 and 30 percentage points, for example, for FEF25 15% females compared with 26% males. Conclusions: Among extremely prematurely born school children airway function was significantly worse in males.